Distillation operation - Kister, Henry Z. (McGraw-Hill's AccessEngineering., 2013)
"There are many books that discuss distillation, but there is only one that concentrates on giving readers practical guidelines for operation, troubleshooting and control. Distillation Operation is that book. Its contents revolves around over 300 actual case histories of distillation problems. Each problem and its solution are briefly described, and the lessons learned are included in the practical guidelines that make up the book. Carefully focused, the book shows you how over 90 percent of all column malfunctions occurred in the past, how they were solved, and how to prevent them in the future. Starting with column internals and their malfunctions, it progresses to installation, commissioning, startup and normal operation before surveying the auxiliary system and the column automatic controls--how they should be, how they can go wrong, and how you can repair them. This book offers the best available compendium of do's and don'ts, good practices, and guidelines for trouble-free design; operation and troubleshooting for inlets and outlet s; distributors; avoiding tray damage; installation; commissioning and startup techniques; column flood and efficiency testing; pressure, and temperature and boilup control.".